Flexor pollicis longus (FPL) tendon hypoplasia: A case report and literature review - Dheer, Sachin (Radiol Case Rep, 2019)
An 18-year-old female presented with long-standing inability to flex her left thumb. MRI of the left thumb revealed flexor pollicus longus (FPL) tendon hypoplasia, and subsequent ultrasound of the bilateral thumbs confirmed a left-sided hypoplastic FPL tendon. Structural integrity of the left FPL tendon was confirmed during surgical examination under anesthesia. Multiple congenital anomalies of the FPL have been described, but FPL tendon hypoplasia and its appearance on imaging are rarely reported. This case demonstrates the diagnosis of FPL tendon hypoplasia on MRI, ultrasound, and surgical examination under anesthesia; and demonstrates the importance of including this entity in the differential diagnosis for impaired thumb flexion.